Ammonia emission time profiles based on manure transport data improve ammonia modelling across north western Europe. (April 2016) - Hendriks, C.; Kranenburg, R.; Kuenen, J.J.P.; Van den Bril, B.; Verguts, V.; Schaap, M.
Abstract: Accurate modelling of mitigation measures for nitrogen deposition and secondary inorganic aerosol (SIA) episodes requires a detailed representation of emission patterns from agriculture. In this study the meteorological influence on the temporal variability of ammonia emissions from livestock housing and application of manure and fertilizer are included in the chemistry transport model LOTOS-EUROS. For manure application, manure transport data from Flanders (Belgium) were used as a proxy to derive the emission variability. Using improved ammonia emission variability strongly improves model performance for ammonia, mainly by a better representation of the spring maximum. The impact on model performance for SIA was negligible as explained by the limited, ammonia rich region in which the emission variability was updated. The contribution of Flemish agriculture to modelled annual mean ammonia and SIA concentrations in Flanders were quantified at respectively 7–8 and 1–2 μg/m 3 . A scenario study was performed to investigate the effects of reducing ammonia emissions from manure application during PM episodes by 75%, yielding a maximum reduction in modelled SIA levels of 1–3 μg/m 3 during episodes. Year-to-year emission variability and a soil module to explicitly model the emission process from manure and fertilizer application are needed to further improve the modelling of the ammonia budget. Highlights: Time profiles of ammonia emissions from manure application were modelled using manure transport data for north western Europe. Meteorological dependent emission characteristics for ammonia increased model performance for ammonia. Source attribution modelling shows a 1–2 μg/m 3 contribution of Flemish agriculture to domestic PM concentrations.